(untitled) (Eurasian Journal of Philology Science and Education, 2020)
In recent years, the activity-based approach to languages teaching has become a subject of particular attention. The purpose of the article is to investigate the activity approach in teaching professional Russian to the bachelor-students of natural sciences. The article proposes a methodology for organizing and conducting students’ project activities when teaching professional Russian in order to use a special language in situations as close as possible to professional communication. The goals, objectives and purpose of the course “Professional Russian Language” are being determined. The essence of the concept of “project activity” is revealed from linguodidactic positions, which is based on the use of the language in situations maximum close to the conditions of real communication; with emphasis on independent work of students (individual and team); the selection of topics of great interest to students and directly related to the conditions, under which the project is being implemented; selection of language material, types of tasks, establishing a sequence of work in accordance with the theme and purpose of the project, visual representation of the outcomes. Depending on the dominant type of speech activity, there is given the projects typological groups classification: research, creative, role-playing, informative, project-oriented. Particular attention is paid to the description of the role-playing business project. The analysis shows, that the use of design technologies in teaching professional Russian language contributes into the formation of intellectual, creative and communicative skills.